Zoning based on the functions of the geography education field laboratory in the galunggung mountain area, west java-indonesia. Issue 1 (1st November 2022) - As'ari, R; Rohmat, D; Ningrum, E; Yani, A
Abstract: Open space offers opportunities that are not found indoors in the learning process. The physical environment contributes to students' learning by exploring their abilities. This requires the world community to be aware of the location, understand the relationship between locations, cause-effect (analysis), and the consequences caused internally and externally. The need for a comprehensive geographic study model is needed, so that it can show the public a geographical solution to certain environmental problems. Geography Education field laboratory can be used as a support for learning in the classroom. The method of zoning for the analysis of needs for field laboratory studies in the Mount Galunggung area is carried out by identifying needs, by referring to the learning outcome program and course learning. Types of integrated laboratories located in faculty or university study centers, or technical implementing units that provide education and / or training with supporting equipment for categories I, II, and III, and managed materials are general and special category materials to serve research activities, and community service, students and lecturers. Based on the results of field surveys and satellite image analysis which refers to suitability indicators for the development of potential Geography education field laboratories, the Gunung Galunggung area has 5 stations/ zones to be used as a Geography Education Field Laboratory.